Flutuação populacional de Glycaspis brimblecombei Moore, 1964 (Hemiptera: Aphalaridae) em plantios comerciais de Eucalyptus spp. em uma microrregião do Estado de São Paulo - Matheus, Luana Isabela (Universidade Federal de São Carlos, 2024)
In Brazil, silviculture of exotic species is a growing activity and species of the genus Eucalyptus are widely exploited for the production of paper and pulp. However, eucalyptus production in Brazil faces some challenges, such as the incidence of pests such as the shell psyllid, an exotic insect that can threaten the productivity of commercial areas. Therefore, the present study aimed to verify the population fluctuation of shell psyllid nymphs in a microregion of the state of São Paulo in 2021 in three distinct eucalyptus clones and to evaluate how meteorological variables and clones influence infestation levels. For this purpose, young commercial plantations of three distinct clones were sampled from january to december 2021 regarding nymph infestation levels, maximum and minimum temperatures, water deficit, and precipitation. The sampled data were subjected to principal component analysis (PCA) to obtain the results inherent to the correlation of variables and to the Kruskal-Wallis test and Dunn's test at 5% significance. It was observed that the genetic material and water deficit positively influenced PC1, a component responsible for 43.2% of the variability of the observed results and, consequently, of the nymph infestation levels. For the average nymph infestation levels in the clones, there was a statistical difference between the pairs of clones 2–3 and 2–1, where clones 1 and 3 presented the highest average nymph infestation levels. In addition, the population peaks of the shell psyllid nymphs were higher during the dry season.
Population fluctuation of Glycaspis brimblecombei Moore, 1964 (Hemiptera: Aphalaridae) in commercial plantations of eucalyptus spp. in a microregion of the State of São Paulo
Keywords: Manejo integrado de pragas; Psilídeo-de-concha; Amostragem; Eucalipto; Integrated pest management; Shell psyllid; Sampling; Eucalyptus; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE